Moore–Gibson–Thompson model with the influence of moisture diffusivity of semiconductor materials during photothermal excitation - El-Sapa, Shreen; Becheikh, Nidhal; Chtioui, Houda; Lotfy, Kh.; Seddeek, M. A.; El-Bary, Alaa A.; El-Dali, A. (Frontiers in Physics, 2023)
In the present work, the semiconductor material is used to study the moisture diffusivity when a modified Moore-Gibosn-Thompson (MGT) model is taken into account. The influence of moisture concentration is included in the governing equations throughout the photothermal (PT) transfer process. Based on the dissimilar relaxation durations of the coupled optoelectronic and thermoelastic waves, the Moore-Gibosn-Thompson model is used to investigate the issue at hand. The method of Laplace transform is used to obtain analytical solutions for the physical quantities, constitutive relationships, elastic waves, carrier density, heat equation conduction, and moisture diffusivity for the thermos-elastic medium. To extract the primary physical quantities in the space-time domain, the boundary conditions, temperature, plasma, displacement, and mechanical stress are inverted numerically using the Laplace transform. The effect of the new parameter like the reference moisture parameter with various values is discussed graphically on the primary physical quantities. The comparison between the silicon and germanium takes into account to achieve the numerical computations.